Indeks Keberlanjutan Integrasi Tanaman dengan Ternak (Crop Livestock System) di Kuamang Kuning - Syarifuddin, Hutwan (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
Kuamang Kuning is  one of animal supplied area in Jambi Province. It has not  been yet  exploited such as optimal potential land for farm. Eventhough conversion  of land and  quality were decreased to experience. To increase potency of farm hence integration crop and livestock (crop-livestock system) require to be developed in order to undergo the sustainable agriculture development. Efficiency  on farm can be use internal input because meaning to lessen use of external input which must be bought. Sustainable indexs of  pattern of CLS 57.12 indicating that activity of CLS sustainable enough. Strategy which can be used to farm development is moderate-optimistic. As for key factors for implementation of the strategy  were: (1) farmer group, ( 2) cage fertilize exploiting  and ( 3)governmental subsidy.